Frequency of Different Bacteria and their Antibiotics Sensitivity Pattern in Chronic Osteomyelitis (Journal of Pakistan Orthopaedic Association, 2020)
Objective: To determine the frequency of different bacteria and their antibiotic sensitivity patterns in patients presenting with chronic Osteomyelitis.Methods: This descriptive study was conducted in Orthopedics and Trauma unit District Headquarter Hospital Daggar, Bunir, Khyber Pakhtunkhwa and Lady Reading Hospital Peshawar from 12th August 2016 to 3rd February 2019. Bone biopsy or sequestrum was taken from all patients of long bones of chronic osteomyelitis fulfilling the inclusion criteria and sent to laboratory for culture and sensitivity.Results: The total number of patients enrolled in our study were 193. Majority (78.76%, n=152) of patients yielded positive growth on culture while no growth was documented in 41(21.24%) patients. Staphylococcus aureus was the most common bacteria(64.36%, n=97) followed by Pseudomonas Aeruginosa (17.10%,n=26), E. Coli (11.84%,n=18) and Proteus Mirabilis(7.24%,n=11).Maximum antibiotic sensitivity(> 90%) was noted for Vancomycin and Fusidic Acid while maximum resistance(35.05%,n=34) was noted for Penicillin.Conclusion: Staphylococcus Aureus was the most common bacteria isolated. Majority of isolated bacteria were sensitive to Vancomycin and Fusidic acid.